Book review: Coastal wetlands of the world: geology, ecology, distribution and applications, by David B. Scott, Jennifer Frail-Gauthier and Petra J. Mudie (eds), 2014. Cambridge University Press, Cambridge, UK. 351 pages. Paperback: price 65.00, ISBN: 9781107628250; Hardback: price 120.00, ISBN 9781107056015 - Pawłowski, Dominik (Geologos, 2021)
Book review: Coastal wetlands of the world: geology, ecology, distribution and applications, by David B. Scott, Jennifer Frail-Gauthier and Petra J. Mudie (eds), 2014. Cambridge University Press, Cambridge, UK. 351 pages. Paperback: price 65.00, ISBN: 9781107628250; Hardback: price 120.00, ISBN 9781107056015